2019
DOI: 10.1080/02670844.2019.1653597
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behaviour of borided Incoloy 909

Abstract: The oxidation behaviour of Incoloy 909 superalloy subjected to diffusion boronizing treatments was studied at 750 and 850°C in atmospheres of dry air and a mixture of dry air + water vapour for times up to 10 h. The oxidation behaviour of the coated samples was described by the parabolic rate law with activation energies of 26 and 21 kJ mol −1 when oxidation was conducted in dry air or in the mixture dry air + water vapour respectively. Oxidation kinetics of the boronized coatings were sensitive to temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Relevant data are taken from other research. [42,44,45] The calculated critical weight percentage should be up to 3.1 wt% to promote the formation of Al 2 O 3 . In addition, prior research showed that the weight percentage of Al in the superalloy should be greater than 5.7 wt% to ensure sufficient supplement of Al solution to form a dense and complete Al 2 O 3 layer.…”
Section: Growth Mechanism Of Oxidation Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant data are taken from other research. [42,44,45] The calculated critical weight percentage should be up to 3.1 wt% to promote the formation of Al 2 O 3 . In addition, prior research showed that the weight percentage of Al in the superalloy should be greater than 5.7 wt% to ensure sufficient supplement of Al solution to form a dense and complete Al 2 O 3 layer.…”
Section: Growth Mechanism Of Oxidation Layersmentioning
confidence: 99%
“…The oxidation activation energy is also a key parameter reflecting the oxidation resistance of superalloys. Researchers have investigated the oxidation activation energy of the superalloy using kinetic curves of mass gains at two temperatures, [32,34,45] which has valuable reference to evaluate the service life. In the present work, the Co-Ni-Albased superalloy shows good oxidation resistance at 1073 K, but the oxidation resistance decreases at 1173 K, indicating that applications of the superalloy might be limited to 1173 K. Consequently, obtaining the activation energy with just two groups of data at different temperatures should be still acceptable with the oxidation temperature gap (increment of temperature) reaching to be 100 K which is enough for the experimental temperatures.…”
Section: Oxidation Kinetics and Oxidation Activation Energymentioning
confidence: 99%